Exposure of wild boar to Influenza A viruses in Bavaria: Analysis of seroprevalences and antibody subtype specificity before and after the panzootic of highly pathogenic avian influenza viruses A (H5N8). (13th May 2021) - Schülein, Anika; Ritzmann, Mathias; Christian, Jürgen; Schneider, Katharina; Neubauer‐Juric, Antonie
Abstract: Swine influenza A viruses (S‐IAV) circulate in wild boar populations worldwide. Subtypes primarily reflect those actually present within the respective pig industry. Accordingly, infections with swine H1N1, H1N2 and H3N2 have been reported for several regions of Germany. As pigs are susceptible not only to S‐IAV but also to avian and human influenza A viruses, it is necessary to consider the possibility that new reassortant viruses with pandemic potential may arise in these new hosts. Therefore, in this study the impact of recent IAV epidemics on antibody prevalences in Bavarian wild boar was assessed. Important events considered were the H1N1pdm09 pandemic, which affected humans and swine, and the highly pathogenic avian influenza (HPAI) H5N8 panzootic in 2016 and 2017, affecting wild and domestic birds. IAV seroprevalences were determined analysing 1, 396 samples from before and after the H5N8 panzootic, from various regions in Bavaria, a large administrative region in the South of Germany. Taken together, seroprevalences varied markedly from 1.44% to 12.59%, relative to region and time. However, no discrete correlation was found to population density either in wild boar or in pigs. Antibodies against H1N1 were the most prevalent. In addition, antibodies were detected reacting against H1N2 and against H1pdmNx reassortant viruses, already known to circulate in domestic pigs in Bavaria and notably also against the avian influenza A virus H5N8; the latter in samples taken in 2017. These results confirm the exposure of wild boar to IAV of diverse origin and the increasing variability of S‐IAV present in the field. The necessity for continuous IAV surveillance not only of domestic swine but also of wildlife is emphasized.